Competing Partisan Regimes and the Transformation of the Voting Rights Act, 1965-2015 - Jesse H. Rhodes (Transatlantica)
On June 26, 2013, the Supreme Court struck down the coverage formula enabling federal preclearance of proposed voting changes in jurisdictions with documented histories of racial discrimination. This paper interprets this event as the most recent symptom of a long-term partisan and institutional struggle over the scope of federal voting rights enforcement. Lingering liberal Democratic influence in Congress, coupled with conservatives’ fears of violating the norm of racial equality, obstructed Republican diminution of federal voting rights enforcement via legislation. Consequently, Republicans turned to lower-profile administrative and especially judicial venues, which offered conservative elected officials chances to circumscribe voting rights enforcement while simultaneously maintaining a public facade of support for the norm of racial equality. Over time, this dynamic has yielded a situation in which the Court has come to serve as the judicial arm of the Republican Party, at least in the realm of voting rights.